ANALISIS PENGARUH HUMAN CAPITAL ,ANGKATAN KERJA, DAN PENDIDIKAN TERHADAP PENDUDUK MISKIN SUMATERA UTARA TAHUN 2006-2022 - Roy Kristanto Lumban Tobing; Darwin Sinaga; Inda Serfina Tarigan; Sophia Amanda; Nathaline Br Tambunan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
Poverty is a classic problem that is almost impossible to eradicate from the face of the earth. The current problem of covid is also exacerbating the increase in the number of poor people both globally and in Indonesia, especially in the North Sumatra province. The aim of this research is to find out and analyse the influence of the Labour Force, IPM and Education on the poor population in the North Sumatra Province. This study uses secondary data obtained from the Central Statistical Authority of North Sumatra Province 2006-2022. Data testing on this study was carried out using eviews-10. As for the results of this study, a) The results of the study show: 1) In the short term the variable Labour Force has a negative and insignificant relationship to the Poor Population in the Northern Sumatra Province in 2006-2022. In the long term the labour force variable has a positive and significant impact on the poor population in North Sumatra province in 2006 - 2022. 2) In the Short term the Variable IPM has negative and non-significant relation to the poor people in the South Sumatra Provincial in 2006 to 2022.